2021
DOI: 10.1038/s41598-020-79535-0
|View full text |Cite
|
Sign up to set email alerts
|

Severe retinopathy of prematurity is associated with early post-natal low platelet count

Abstract: Pathophysiology of retinopathy of prematurity (ROP) still presents a gap. Lately blood tests parameters of premature infants have been measured at different times of ROP, attempting to detect correlations with ROP development and progression. So far, very early post-natal biomarkers, predictive of ROP outcome, have not been detected. Our purpose is to evaluate, in the earliest post birth blood sample, the correlation between routinely dosed blood parameters and ROP outcome. 563 preterm babies, screened accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
1
32
1
1
Order By: Relevance
“…Ultimately, 19 primary studies fulfilled the eligibility criteria and were included in this review: 18 clinical studies and one study with both experimental and clinical sections. All the clinical studies were observational, of which one case series, 17 eight retrospective case-control studies with or without matching, 15,[18][19][20][21][22][23][24] eight retrospective cohort studies, 16,[25][26][27][28][29][30][31] and two prospective cohort studies. 32,33 If studies comprised three groups, 24,27,29,30,33 comparative data were only collected on cases with ROP requiring treatment and the group of infants without ROP.…”
Section: Re Sultsmentioning
confidence: 99%
“…Ultimately, 19 primary studies fulfilled the eligibility criteria and were included in this review: 18 clinical studies and one study with both experimental and clinical sections. All the clinical studies were observational, of which one case series, 17 eight retrospective case-control studies with or without matching, 15,[18][19][20][21][22][23][24] eight retrospective cohort studies, 16,[25][26][27][28][29][30][31] and two prospective cohort studies. 32,33 If studies comprised three groups, 24,27,29,30,33 comparative data were only collected on cases with ROP requiring treatment and the group of infants without ROP.…”
Section: Re Sultsmentioning
confidence: 99%
“…There is significant thrombocytopenia in the blood samples of infants with treatment-requiring ROP, and this could be a predictor of disease progression ( 103 ). Platelet mass index is a reliable monitoring indicator for the prognosis of ROP in very premature newborns ( 104 ).…”
Section: Candidates Of Novel Potential Biomarkersmentioning
confidence: 99%
“…Therefore, there is an urgent need of standardizing evaluation criteria and identifying early indicators for ROP development. In this respect, a recent retrospective Italian study reported that early platelet counts were significantly reduced in newborns who later developed severe ROP which required treatment, but not in those who never developed ROP [ 48 , 49 ] suggesting that platelet count may be used to detect in advance premature infants prone to ROP development. Recently, a new prediction model for ROP, the Postnatal Growth and ROP (G-ROP), which was originally developed in 2018 and validated in a North American cohort of preterm infants [ 50 ], has been also validated in Italy [ 51 ].…”
Section: Rop In Italymentioning
confidence: 99%